2011
DOI: 10.1007/s00253-011-3419-8
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression, activity screening and functional characterization identifies three novel endo-1,4-β-glucanases that efficiently hydrolyse cellulosic substrates

Abstract: The hydrolysis of cellulose into fermentable sugars is a costly and rate-limiting step in the production of biofuels from renewable feedstocks. Developing new cellulase systems capable of increased cellulose hydrolysis rates would reduce biofuel production costs. With this in mind, we screened 55 fungal endoglucanases for their abilities to be expressed at high levels by Aspergillus niger and to hydrolyze amorphous cellulose at rates significantly greater than that obtained with TrCel5A, one of the major endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
2
32
2
Order By: Relevance
“…These results differ from previous thermal stability results on testing of G. trabeum Cel12A against CMC in similar conditions, which showed a much shorter half-life of 2 hours [24].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results differ from previous thermal stability results on testing of G. trabeum Cel12A against CMC in similar conditions, which showed a much shorter half-life of 2 hours [24].…”
Section: Discussioncontrasting
confidence: 99%
“…We speculate that similar molecular organization can facilitate interactions of G. trabeum Cel12A with none-crystalline polysaccharides. Furthermore, we and others [24] showed that GtCel12A displays activity, albeit low, towards the commercial cellulose Avicel. It should be noted that the commercial microcrystalline cellulose, Avicel (Fluka, St Louis, USA) and Sigmacell (Sigma-Aldrich, St Louis, USA) contains amorphous regions and are heterogeneous substrates.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Both activity and level of expression were compared to that of TrCel5A, one of the major endoglucanases from T. reesei. This screen identified three EGLs, from species Aureobasidium pullulans, Gloeophyllum trabeum and Sporotrichum thermophile with expression levels and hydrolysis performances superior to those of the Trichoderma enzyme [87].…”
Section: Expression Of Cellulases In Fungimentioning
confidence: 99%
“…The cellobiohydrolase contained six times more Nlinked glycans when expressed in A. niger, and its activity was reduced, underlining the critical effect of post-translation modifications on recombinant cellulases [86]. Recently, a library of EGLs from various fungi were cloned and expressed in A. niger [87]. Both activity and level of expression were compared to that of TrCel5A, one of the major endoglucanases from T. reesei.…”
Section: Expression Of Cellulases In Fungimentioning
confidence: 99%